Hyperspectral calibration database on cooked cassava to predict dry matter content - Meghar, Karima; Tran, Thierry; Ospina Portilla, Maria Alejandra (2023)
This database contains 100 NIR average spectra of HSI images of cooked cassava root acquired in CIAT (Colombia), by using hyper spectral camera Specim FX17. Cassava roots were harvested from 07/03/2022 to 11/03/2022 in CIAT (Colombia) and analysed immediately after cooking. Twelve roots were used and each root is divided into six semicylinders. The semicylinders number 03,43,103 and 114 were used for HSI and DM measurements. Data was acquired using MEGHAR, K., DAVRIEUX, F., & ALAMU, E. (2020). SOP for Hyperspectral Imaging Analysis of Fresh RTB Crops. High-Throughput Phenotyping Protocols (HTPP), WP3. Montpellier, France: RTBfoods Project Report, 14 p. (2022-10-19)